Production of Ceramic Materials from High Loading of Palm Oil Fuel Ash mixed with recycled Soda-Lime-Silica glass - Hasnan, Hanisah Husna; Mohd Zul Hilmi Bin Mayzan (Enhanced Knowledge in Sciences and Technology, 2022)
The production of ceramic materials from high loading of palm oil fuel ash (POFA) mixed with recycled soda-lime-silica (SLS) is reported in this paper. Hence, experiment was conducted to investigate which composition of POFA and SLS gives the best result to produce ceramic and to characterize the physical and structural properties of the sample. The composition of POFA and SLS was altered within 30 wt% to 80 wt% and sintered at a temperature of 900℃ for 2 hours. Powder for each raw material is prepared separately with a similar method includes grinding and sieving with 50 µm micro-siever and pelleted at a pressure of 3 tons for 5 minutes. The physical and structural properties of the samples are studied under the percentage of mass loss, density, porosity, chemical bonding, crystalline structure, and surface morphology by using high accuracy balance (4 d.p.), Archimedes’ method, Fourier Transform Infrared (FTIR), Bruker D2 PHASER 2nd generation X-ray Diffraction (XRD) and COXEM EM-30AX scanning microscopy (SEM) respectively. The result showed at 80 wt% POFA mixed with 20 wt% SLS has the highest amount of silicon dioxide, greater bulk and powder density which is 2.1450 and 2.5765 respectively and with the reduction of POFA, the overall density is reduced. The highest quartz peak can be seen in the 80 wt% POFA sample proved by XRD results. FTIR shows a greater Si-O bond at 80 wt% POFA and 20 wt% SLS compared with other samples.